COVID-19 and fiscal-monetary policy coordination: Empirical evidence from India - Lekha Chakraborty; Harikrishnan S (Levy Economics Institute of Bard College, 2022)
Against the backdrop of the COVID-19 pandemic, this paper analyzes the economic stimulus packages announced by the Indian national government and tries to identify some plausible fiscal and monetary policy coordination. The shrinking fiscal space due to revenue uncertainties has led to a theoretical plausibility of a reemergence of finite monetization of deficits in India. However, the empirical evidence confirms no direct monetization of the deficit.
Keywords: E58; E62; E63; 330; Fiscal-Monetary Policy Coordination; Fiscal Deficits; Monetization; COVID-19